Automatic Speech Emotion Recognition Using Hybrid Deep Learning Techniques - Rasheed, Bilal Hikmat; Yuvaraj, D.; Alnuaimi, Saif Saad; Priya, S. Shanmuga (International Journal of Intelligent Systems and Applications in Engineering, 2024)
An emerging field of research is the advancement of deep learning techniques for speech emotion recognition. The current scenario of human-computer interaction is being significantly impacted by and altered by speech recognition technologies. In human-computer interaction, developing an interface that can sense and react accurately like a human is one of the main crucial challenges. As a result, the Automatic Speech Emotion Recognition (ASER) system has been developed. It extracts and identifies important data from voice signals to classify various emotional categories. The novel advancements in deep learning have also led to a major improvement in the ASER system’s performance. Numerous methods, including some well-known speech analysis and classification approaches, have been used to derive emotions from signals in the literature on ASER. Recently, deep learning methods have been suggested as an alternative to conventional methods in ASER. The main goal of this research is to use deep learning techniques to analyze different emotions from speech. Because deep learning networks have sophisticated feature extraction processes, they are frequently utilized for emotional classification, in advance of traditional/machine learning systems that depend on manual feature extraction before classifying the emotional state. To extract features and identify different emotions depending on input data, the authors have implemented the most efficient hybrid deep learning algorithms, CNN+LSTM. By training and testing the suggested network algorithm with the standard dataset, the authors, accordingly, achieved the highest accuracy.